Cryptocurrency Assets in Contemporary Fiqh Muamalah Perspective: Shariah Legitimacy, Regulatory Implications, and Global Islamic Financial Stability - Sitti Fatimah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
The rapid proliferation of cryptocurrency assets across global financial markets has prompted urgent inquiry within Islamic jurisprudence regarding their permissibility under fiqh muamalah. This study examines the shariah legitimacy of cryptocurrency assets through the lens of contemporary Islamic legal reasoning, evaluating their compliance with foundational principles including the prohibition of riba (usury), gharar (excessive uncertainty), and maysir (gambling). Employing a qualitative normative-juridical methodology supported by comparative analysis of fatwas issued by major Islamic scholarly bodies—including the Majma' al-Fiqh al-Islami, the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), and national fatwa councils in Indonesia, Malaysia, and Qatar—this research synthesizes divergent scholarly positions and assesses their regulatory implications for Islamic financial institutions globally. Findings reveal that while a majority of contemporary scholars express reservations regarding speculative cryptocurrencies such as Bitcoin and Ethereum in their current form, a growing body of opinion acknowledges the potential shariah-compliance of asset-backed digital tokens and Central Bank Digital Currencies (CBDCs) developed within an Islamic regulatory framework. The study further argues that harmonized international regulatory standards grounded in maqasid al-shariah are essential for safeguarding Islamic financial stability. This research contributes to the nascent but critical discourse at the intersection of digital finance and Islamic law, offering policy recommendations for regulators, Islamic financial institutions, and scholars navigating the complex digital economy.